2008
DOI: 10.1080/00016480802008165
|View full text |Cite
|
Sign up to set email alerts
|

Universal newborn hearing screening programs in Italy: survey of year 2006

Abstract: In Italy UNHS coverage had undergone a steep increase from 29.3% in 2003 (156,048 newborns screened) to 48.4% in 2006 (262,103 screened). The majority of UNHS programs were implemented in the two most economically developed areas, i.e. in the north-west area (79.5%, 108,200 of 136,109 births), and in the north-east area (57.2%, 52,727 of 92,133 births), while a limited diffusion still remains in some areas, typically in the islands (11.3%, 7158 of 63,460 births).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…The aim of such programs is to identify hearing impairments present at birth, overall medium and severe (bilateral, >= 40 dB HTL between 0.5 and 4 KHz) [15-21,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…The aim of such programs is to identify hearing impairments present at birth, overall medium and severe (bilateral, >= 40 dB HTL between 0.5 and 4 KHz) [15-21,6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…9 An overview of universal newborn hearing screening (UNHS) in 24 European countries from [2004][2005][2006] showed that in several countries UNHS programmes reached more than 95% of all neonates, but in many other countries programmes were recently introduced or were only partially functioning. 10 Other reports on national neonatal hearing screening programmes raise issues on implementation, test procedures, type of tests, coverage, detected cases of hearing loss, and costs. [11][12][13][14][15][16][17][18][19] A Health Technology Assessment review in 2008 20 re-examining the cost-effectiveness of vision screening up to age 4-5 (following previous report in 1997 21 ) found that, based on the accepted value of a Quality-adjusted life year, the cost-effectiveness of screening for amblyopia depends on the long-term utility effects of unilateral vision loss and that there was currently no sustainable evidence of utility loss that would render any form of screening likely to be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ideal hearingscreening test for children has yet to be defined and local circumstances may make variations necessary depending on to medical equipment (ABR or/and EOAEs) and, presence/absence of audiological specialist [19][20][21]. This pilot study carried out in Sciacca hospital from the beginning of 2003, was set out to determine the feasibility and effectiveness of hospital-based UNHS by non-specialists for promoting early detection of congenital and early onset hearing loss in Western Sicily that still now is lacking [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of early detection can only be realized if an effective newborn hearing-screening programme is performed. In Italy [6], as in other developed countries in the most of birth centres is not present a specialist audiologist, therefore the neonatal nurse who understands the consequences of undetected hearing loss is an excellent position to emphasize the point. In fact it plays an essential role performing the screening, charting the results and informing the parents about the screening outcomes.…”
Section: Introductionmentioning
confidence: 99%